2006
DOI: 10.1111/j.1365-2982.2006.00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Postinfectious irritable bowel syndrome may occur after non-gastrointestinal and intestinal infection

Abstract: Postinfectious functional gastrointestinal disorders (FGIDs) may not be specific to gastroenteritis. This pilot study aimed to ascertain the 3- and 6-month incidence of functional gut disorders in people with non-gastrointestinal (GI) infection, gastroenteritis and healthy controls. This was a prospective study of three cohorts recruited from hospital (non-GI infections) and the community (others). FGIDs were diagnosed using self-completed Rome II modular questionnaires administered at baseline, 3 and 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 16 publications
0
34
0
3
Order By: Relevance
“…Various mechanisms, including gastrointestinal dismotility and visceral hypersensitivity, have been extensively studied in IBS [8][9][10] , but recent interest has also been associated with, or directed to the possible participation of the intestinal mucosa in the pathophysiology of IBS [11][12][13]17] . Several lines of evidence suggest that IBS may be associated with inflammation in the ileal or colonic mucosa, and at least in a subset of patients with IBS, the mucosal immune system seems to be activated [11,[15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various mechanisms, including gastrointestinal dismotility and visceral hypersensitivity, have been extensively studied in IBS [8][9][10] , but recent interest has also been associated with, or directed to the possible participation of the intestinal mucosa in the pathophysiology of IBS [11][12][13]17] . Several lines of evidence suggest that IBS may be associated with inflammation in the ileal or colonic mucosa, and at least in a subset of patients with IBS, the mucosal immune system seems to be activated [11,[15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the frequency of IBS is associated with psychological stress, food intolerance (adverse reaction to a specific food or ingredient that is not immune mediated or associated with psychological phenomena), intestinal infections, and even previous abdominal surgery [3,7,12,[20][21][22][23][24][25] . Dunlop et al [16] have reported that patients with subtype D-IBS (pos-infectious and non-infectious origin) have a more pronounced permeability increase in the proximal intestine compared with controls and those with C-IBS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that acute infectious gastroenteritis (GE) can increase the risk of IBS, with several studies demonstrating that a significant number of GE patients develop PI-IBS [1,2,[18][19][20][21][22][23]. Campylobacter, Shigella, Salmonella and Escherichia coli infections as well as viral agents, including norovirus, and parasites have been associated with PI-IBS [5,21,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…042. For the duration of PI-IBS, several long-term follow-up studies were assessed [15,16,[22][23][24][25]. Based on these studies, we assumed for PI-IBS provoked by bacteria an average duration of 5 years [14].…”
Section: Dalysmentioning
confidence: 99%